PANDANGAN ABUL AâLA AL MAUDUDI TENTANG NEGARA ISLAM - Nurlidiawati, Nurlidiawati (RIHLAH, 2014)
This paper explore Abul Aâla al-Maududiâs thought of Islamic nation. he was eager to realize the Islamic governmentÂ because he wants the Muslims as a whole run the government in accordance with the instructions of the Koran holy book and ordinances as well as the implementation of the rules as they never practiced by the Prophet. Sovereignty is in God, the laws in force must be based on Islamic shariah. The ideas of Maududi of an Islamic state foundation on leadership Khulafa al-Rashidun.